Making Human Rights a Reality - Emilie M. Hafner-Burton (Princeton University Press, 2013)
Two decades ago, I worked in the blacksmithing industry. I had a college degree under my belt—with concentrations in political science, philosophy, and women’s studies. And I was apprenticing with artists who taught me the trade of blacksmithing. Then I took a hiatus that changed my life. I won a fellowship, moved to Geneva, Switzerland, and started working for an international nongovernmental organization dedicated to the promotion of human rights and disarmament. That job, and another that followed, put me inside the United Nations. There, I experienced firsthand how international laws are made and managed through a sprawling bureaucracy involving different—often- mismatched— interests, competences, and intentions. I witnessed the potential of international cooperation. I also witnessed the power of governments and individuals to stymie it. I saw the hair-pulling frustrations of paperwork, official procedures, red tape, and ceaseless committee meetings. And I saw the powerlessness of many advocacy organizations to have much direct impact on this system. I left. I am still grateful for this experience, which set me on the path I’m on today and motivated this book. Now I am a political scientist, university professor, and codirector of the Laboratory on International Law and Regulation.1 Our mission at this laboratory is social science research to explore when and why international laws actually work. We aim to craft more effective solutions to global problems, such as the persistence of human rights violations that contribute to the suffering of millions of people. I write and teach courses on international law, human rights, political economy, public policy, and other topics. This book has been many years in the making. It’s based on a great deal of research—some that I’ve conducted, and much more by other scholars in a lot of fields, including anthropology, criminology, history, law, political science, psychology, and sociology. It represents my thinking after nearly two decades of experience and investigation about the problem of human rights as well as the efficacy of the international legal and foreign policy systems created in response.One reason it’s taken so long to write this book is that I’ve come to realize that human rights scholarship can’t fit neatly into any single field. Research (including my own) that concerns human rights tends to be specialized, focused on the debates and methods that are germane to a particular academic discipline. That’s understandable because it’s impossible to be an expert in all subjects. But it’s also a hurdle to understanding the problem of human rights and crafting solutions, which don’t fit neatly in our academic boxes.